EPIDEMIOLOGI DAN DIAGNOSIS KEDOKTERAN LABORATORIK INFEKSI VIRUS H1N1 - Sembiring, J; Sianipar, O (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
H1N1 virus is an influenza virus family orthomyxoviridae, which clinical symptoms consist of: fever, cough, sore throat and headache. The virus can spread from person to person through airborne droplets and so a good infection control in the community or in healthworkers is needed, for instance by washing hands properly and PPE (Personal Protective Equipment). In October 4, 2009 there were over375.000 reported cases in which 4500 people were died. On June 11, 2009 the WHO stairs announced that H1N1 is the first pandemicin the 21st century. (The Indonesia people province was infecting by H1N1with 20 deaths until August 5, 2009). The purpose of thisarticle is to find out the epidemiological aspects as well as the diagnosis of influenza A H1N1 virus. From the website was found about1.110.000 sources, and after downloading them are selected as they are written only in the bibliography. From the searched informationobtained, it was known that H1N1 infection diagnosis begins with the discovery of heat (temperature ≥ 100° F [37.8° C]) and cough or sore throat. No cause other than influenza that is called with ILI was found. The informed laboratory examination is divided into three parts are confirmed if ILI was found as well as the virus in the throat or nasal swab by RT-PCR and/or virus culture; probably the ILIhas positive results of influenza A RT-PCR, but if the results are negative including the laboratorial findings, the basis of epidemiologyin this case was only suspected. Laboratory plays an important role in the establishing of the H1N1 infection diagnosis Rapid diagnosisis important to reduce infection, to protect patients from complications by antiviral treatment in the right time and also to provideimmediate information for the public.